Strengthening the Pancasila Student Profile through Local Diversity Activities at SMP Negeri 12 Palu - Mentemas, Abelia; Nugroho, Fajar; Iskandar; Suyuti (Kirana Publisher (KNPub), 2025)
Strengthening the Pancasila Student Profile through Local Diversity Activities at SMP Negeri 12 Palu. Study Program of History Education, Department of Social Science Education, Faculty of Teacher Training and Education, Tadulako University. Supervisor: Fajar Nugroho. This study aims to: (1) Describe the process of strengthening the Pancasila Student Profile through local diversity activities at SMP Negeri 12 Palu; (2) Explain the impact of strengthening the Pancasila Student Profile on students through local diversity activities; and (3) Identify challenges and obstacles in implementing the strengthening of the Pancasila Student Profile through local diversity activities. This research employed a descriptive qualitative method with data collection techniques including: (1) observation; (2) interviews; and (3) documentation. The findings show that local diversity activities conducted in the form of Cultural Exhibitions, traditional dances, and other cultural projects actively instill Pancasila values such as mutual cooperation, local diversity, and critical reasoning. However, obstacles remain, such as limited teacher understanding of the P5 module and low student participation. The study concludes that local diversity activities are able to strengthen student character dimensions in line with the Pancasila Student Profile if supported by the consistent and sustainable involvement of the entire school community.